Limitation of The President's Power to Declare a State of Emergency: a Comparison of France, India, and Indonesia - Muhammad Yoppy Adhihernawan; Hernadi Affandi (Jurnal Penelitian Hukum De Jure, 2022)
The state must declare a state of emergency under certain conditions that endanger the safety of the state and society. Limiting the power to the declaration of a state of emergency is essential because this great authority cannot be used according to the President's will, so it is necessary to have restrictive mechanisms so that the President does not misuse the authority to carry out the emergency. However, the Indonesian constitution does not stipulate any restrictions on the powers of the President in declaring a state of emergency. This study aims to determine the dangers of not limiting the President's powers in declaring a state of emergency in the Indonesian constitution by using the arrangements and practices of emergency law in France and India. The approach used in this study is a comparative level that compares the contents of the constitution's text and compares the implementation and history of the constitution. The result of this study is limiting the power of the President in declaring a state of emergency is necessary based on a comparison of arrangements and experiences in France and India. Therefore, Indonesia must restrict the President's power in declaring a state of emergency to its constitution.